Opening the horizons of clinical reasoning to qualitative research: Integrating Qualitative Research in Clinical Reasoning - Díaz Crescitelli, Matías Eduardo; Ghirotto, Luca; Artioli, Giovanna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2019)
Clinical Reasoning (CR) is an important aspect of health professional education and effective practice. It is a complex series of factors and cognitive functions, involving higher-level thinking to define problems, examine the evidence and then making decisions and choices to improve the patient’s physiological and psycho-social state.CR consists of 3 interconnected and interdependent sub-processes: clinical experience and clinical context and Evidence-Based Practice. This essay focuses on the opportunities that Qualitative Research offers during the CR process when the doctor finds the evidence to address a patient’s health problem. Clinicians are often faced with questions that randomized clinical trials or systematic reviews of efficacy studies cannot answer. For this reason, we considered it necessary to offer an expanded view of the process of interpretation of the scientific literature used in daily clinical practice through the complex process of Clinical Reasoning, through the use of studies conducted with qualitative methods, which are able to respond to a different range of clinical questions, and to support studies based on the effectiveness of treatments.